Pros and Cons of Video for Learning Interest in Online Learning Amid Pandemic Covid-19 in University - Yudin Citriadin (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to determine the advantages and disadvantages of video for the level of student interest in learning during the covid-19 pandemic. The COVID-19 pandemic has presented many challenges for lecturers in conducting online learning processes. This means that educators must be able to provide appropriate technology applications so that they can build student interest in learning. The research method uses descriptive qualitative. Data were collected through observation, documents, and interviews. The participants involved are lecturers and students. Data analysis consists of data reduction, data presentation, conclusion drawing and triangulation. The results of the study concluded that video has many advantages in online learning so that it can affect student learning interest in understanding the material compared to without video. Students feel they can study the material anytime at home. However, the shortcomings found are internet network constraints and the creativity of the lecturer in designing videos has not been maximized.